2021
DOI: 10.3390/ijms22052450
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Assessment of a Highly-Active Anti-Inflammatory Exopolysaccharide from Mycelial Fermentation of a Medicinal Fungus Cs-HK1

Abstract: The purpose of this work was to fractionate the complex exopolysaccharide (EPS) from a medicinal fungus Ophiocordyceps sinensis Cs-HK1 based on the molecular weight (MW) range and to assess the in vitro anti-inflammatory activity of different EPS fractions in THP-1 cell culture. The lower MW fraction (EPS-LM-1) showed a much higher anti-inflammatory activity. EPS-LM-1 was identified as a heteropolysaccharide consisting of mannose, glucose, and galactose residues with an average MW of 360 kDa. EPS-LM-1 signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The aqueous solution was then collected and dialyzed against distilled water through a 3500 MW-cut off membrane for 48 h, and then freeze-dried as the final EPS-LM fraction for the following experiments. The deproteinized EPS-LM fraction was mainly composed of a heteroglycan with three monosaccharide residues, Man, Glc and Gal at 7.31: 12.95:1 mole ratio, which were similar to those reported previously [20].…”
Section: Preparation and Analysis Of Eps Fractions From Cs-hk1 Myceli...supporting
confidence: 87%
See 3 more Smart Citations
“…The aqueous solution was then collected and dialyzed against distilled water through a 3500 MW-cut off membrane for 48 h, and then freeze-dried as the final EPS-LM fraction for the following experiments. The deproteinized EPS-LM fraction was mainly composed of a heteroglycan with three monosaccharide residues, Man, Glc and Gal at 7.31: 12.95:1 mole ratio, which were similar to those reported previously [20].…”
Section: Preparation and Analysis Of Eps Fractions From Cs-hk1 Myceli...supporting
confidence: 87%
“…The fermentation liquid was then centrifuged and the supernatant was collected for the isolation of exopolysaccharide (EPS). As reported previously [20], a two-step ethanol precipitation was performed, firstly adding 40% (v/v) ethanol to the fermentation liquid to precipitate the high-MW EPS (EPS-HM) and 80% (v/v) to the remaining liquid to precipitate the lower-MW EPS (EPS-LM). The precipitate was recovered from the liquid by centrifugation (12,000 rpm, 15 min) and freeze dried as the crude EPS fractions.…”
Section: Preparation and Analysis Of Eps Fractions From Cs-hk1 Myceli...mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicate the immense potential of fungal polysaccharides. Additionally, numerous studies have shown that the diversity in the relative molecular weight, monosaccharide composition and content, glycosidic bond type, and sugar-ring configuration in fungal polysaccharides contributes to their structural diversity and functional novelty [ 18 , 19 , 20 , 21 , 22 ]. To date, only a few studies on the isolation, purification, structural characterization, and activity of Mucor fungus polysaccharides have been reported.…”
Section: Introductionmentioning
confidence: 99%